An activity theory study of data, knowledge, and power in the design of an international development NGO impact evaluation. (9th February 2018) - Kelly, Paul Richard
Abstract: International development is now a data‐, information‐, and knowledge‐intensive industry, which some have characterised as "development 2.0." Power relations are rarely foregrounded in this landscape, even though they shape what data and knowledge is constructed or discarded. Impact evaluation is one example of this intensive work, yet evaluation models seldom make power relations explicit or actionable. Furthermore, implicit models of data and knowledge on which impact evaluation processes rely also neglect power and social practice. The resulting problem is that power remains silent in development impact evaluation practice. In response, this article articulates an alternative, using Cultural Historical Activity Theory (CHAT) to analyse impact evaluation activities conducted by a UK‐based philanthropic donor and their grantee in India, a small non‐government organisation (NGO) doing rural development work. The analysis uses CHAT to illustrate how impact data, knowledge, and power are simultaneously generated during professional evaluation activities. The study broadens our view of impact and offers two contributions. Firstly, for researchers in information and communications technology for development (ICT4D) and knowledge management for development (KM4D), it contributes the application of a perspective on social practice, CHAT, to development evaluation. A novel extension to CHAT, the concept of "temporal activity chains, " is put forward to complement the established activity system frame. Secondly, the article demonstrates a practice‐based view of development impact evaluation for researchers and practitioners who wish to acknowledge and respond to the generation of unequal power dynamics during evaluation processes.